How do Economic Structures Reduce Poverty? - Widhi Ariestianti Rochdianingrum; Nur Laily (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Poverty reduction is a government program that is carried out annually. Various efforts were made to reduce poverty levels. One of the efforts that has been taken was to continue to maintain economic growth so that it continued to increase and grow. The existence of economic growth indicates a cycle of economic activity. One of the most important production factors for economic growth is the use of labor absorbed in economic sectors. If a large number of labor are absorbed in production activities, there is an increase in income in the family. The greater one's income level, the more one's welfare level increases. The increase in welfare that exists in society indicates that the poverty level is getting smaller. This research was conducted to test empirically on this matter. In this study, path analysis was used to determine the role of economic structure in reducing poverty with economic growth as a mediating variable. The results of this study indicated that economic growth can mediate the economic structure in reducing poverty levels through the absorption of labor in economic sectors and the resulting increase in output in each economic sector.